Amelioration of diabetes‐induced inflammation mediated pyroptosis, sarcopenia, and adverse muscle remodelling by bone morphogenetic protein‐7. Issue 2 (18th January 2021) - Aluganti Narasimhulu, Chandrakala; Singla, Dinender K.
Abstract: Background: Diabetic myopathy involves hyperglycaemia and inflammation that causes skeletal muscle dysfunction; however, the potential cellular mechanisms that occur between hyperglycaemia and inflammation, which induces sarcopenia, and muscle dysfunction remain unknown. In this study, we investigated hyperglycaemia‐induced inflammation mediating high‐mobility group box 1 activation, which is involved in a novel form of cell death, pyroptosis, diabetic sarcopenia, atrophy, and adverse muscle remodelling. Furthermore, we investigated the therapeutic potential of bone morphogenetic protein‐7 (BMP‐7), an osteoporosis drug, to treat pyroptosis, and diabetic muscle myopathy. Methods: C57BL6 mice were treated with saline (control), streptozotocin (STZ), or STZ + BMP‐7 to generate diabetic muscle myopathy. Diabetes was established by determining the increased levels of glucose. Then, muscle function was examined, and animals were sacrificed. Gastrocnemius muscle or blood samples were analysed for inflammation, pyroptosis, weight loss, muscle atrophy, and adverse structural remodelling of gastrocnemius muscle using histology, enzyme‐linked immunosorbent assay, immunohistochemistry, western blotting, and reverse transcription polymerase chain reaction. Results: A significant ( P  < 0.05) increase in hyperglycaemia leads to an increase in inflammasome (high‐mobility group box 1, toll‐like receptor‐4, and nucleotide‐binding oligomerization domain, leucine‐rich repeat and pyrin domain containing protein 3) formation in diabetic muscle cells. Further analysis showed an up‐regulation of the downstream pyroptotic pathway with significant ( P  < 0.05) number of positive muscle cells expressing pyroptosis‐specific markers [caspase‐1, interleukin (IL)‐1β, IL‐18, and gasdermin‐D]. Pyroptotic cell death is involved in further increasing inflammation by releasing pro‐inflammatory cytokine IL‐6. Structural analysis showed the loss of muscle weight, decreased myofibrillar area, and increased fibrosis leading to muscle dysfunction. Consistent with this finding, BMP‐7 attenuated hyperglycaemia (~50%), pyroptosis, inflammation, and diabetic adverse structural modifications as well as improved muscle function. Conclusions: In conclusion, we report for the first time that increased hyperglycaemia and inflammation involve cellular pyroptosis that induces significant muscle cell loss and adverse remodelling in diabetic myopathy. We also report that targeting pyroptosis with BMP‐7 improves diabetic muscle pathophysiology and muscle function. These findings suggest that BMP‐7 could be a potential therapeutic option to treat diabetic myopathy.